The Influence of Organizational Culture, Situational Leadership and Organizational Commitment on the Work Productivity of PT Maluku Graha Motor Employees - Lawalatta, Merlyn; Lewaherilla, Novalien C.; Pentry, Gerrit M (SEAN Institute, 2024)
The aim of this research is to examine the influence of organizational culture, situational leadership and organizational commitment on employee work productivity. The research took place at PT Maluku Graha Motor. The samples taken were 55 respondents. The data taken is primary data, and the research method used is a quantitative method. The analysis tool used is Multiple Linear Regression. The research results prove that organizational culture, situational leadership and organizational commitment have a significant effect on employee work productivity, both partially and simultaneously.